Studi Pengolahan Lumpur Tinja di Balai Pialam Yogyakarta - Rosita Haerani; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
Sewage Sludge Treatment Plant has an important role in the treatment of sewage waste to reduce the burden of pollutants, especially fecal coliforms in sewage waste. Sewage Sludge Treatment Plant is part of a local on site system or a decentralized system, where this system is widely used in Indonesia. The important role of the Sewage Sludge Treatment Plant is the reason for the need for a study of the Sewage Sludge Treatment Plant so that the performance of the Sewage Sludge Treatment Plant can run optimally and achieve processing goals. This study aims to determine the quality of the processed Sewage Sludge Treatment Plant at Balai Pialam Yogyakarta. The method used is a descriptive method of collecting data at the Sewage Sludge Treatment Plant at the Balai Pialam which is located on Jalan Bantul KM ​​8, Sewon District, Bantul Regency. The data collected is data regarding the processing and quality of treated water from Sewage Sludge Treatment Plant. Furthermore, it is carried out because the analysis with wastewater quality standards for Communal Domestic WWTP activities, Communal Feces WWTP based on DIY Regional Regulation No. 7 of 2016. The results of water testing processed by Sewage Sludge Treatment Plant, show that treated water from Sewage Sludge Treatment Plant cannot be discharged directly into water bodies of total content coliform which is still high with a figure of 2,400,000 MPN/100 mL while for the requirements it is only allowed to be 10,000 MPN/100 mL. So that there is a need for further processing at the WWTP. After the advanced treatment process at the WWTP is carried out, the total coliform is reduced to <1.8 MPN/100 mL and can meet the requirements of the wastewater quality standard so that it is safe to be discharged into the environment. Keywords: Treatment, Sludge, Sewage, Septic Tank, Balai Pialam